POTENSI TEGAKAN HASIL INVENTARISASI HUTAN DI KPH KABUPATEN LEMBATA (STUDI KASUS HUTAN LINDUNG DI DESA LODOTODOKOWA, KECAMATAN LEBATUKAN, KABUPATEN LEMBATA - Atawolo, Maria I. S.; Riwu Kaho, Ludji Michael; Pramatana, Fadlan (Wana Lestari, 2022)
Forest planning is a land use activity that aims to contribute to the community by creating activities that affect ongoing processes or create new processes. Inventory is one of the indispensable components in forest management activities in FMUs. This study aims to determine the potential of stands from forest inventory in Lodotodokowa Village, Lebatukan District, Lembata Regency. The protected forest in Ledotodokowa Village is included in the forest group or the Hadakewa-Labalekang forest area with the forest area in Lodotodokowa Village is 82.06 Ha, the forest area there has not been properly inventoried, so the potential for all forest stands is not known for certain. At the tree level the largest volume is 17,425 m2 on the Hero tree and the lowest volume is 0.022 m2 on the banyan tree. At the tree level, the dominant vegetation type was candlenut with an INP value of 103.299%, the pole level of the dominant vegetation was lamtoro with an INP value of 31.718%, the sapling level of the largest IVI value was 32.566% and the seedling level of the largest INP value was I'aa species of 52.206%. While the type of vegetation that has the lowest IVI value at the tree level is lolopa at 0.560%, the pole level is Cocoa at 0.469% while for the vegetation sapling level with the lowest IVI values are Lape, Spinach, Liha, Noni, Coconut, Waru, Asam, Sengon, and Soursop with an IVI of 0.210%. Meanwhile, for the seedling level, the type of vegetation with the smallest number of INPs was Luge/Java water forest, Lombok, Ranga, Reo, Wuo, and jembulan at 0.239%.